2021
DOI: 10.18421/tem101-56
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Information Flow and Factors for Supplier Selection

Abstract: It is very difficult to select the right supplier from supply base for the global supply chain due to many challenges and problems especially for the developing countries such as Pakistan. In the present study primary data is collected via adopted questionnaire from cases of the total 170 cases from Kotri manufacturing companies of Sindh, Pakistan. For the analysis of gathered data many tests were applied such as reliability test, factor analysis and structural equation modelling in SPSS and AMOS software. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…Fourth, higher self-efficacy and controllability can bring higher green purchase intention and positive green purchase behavior. As the embodiment of individual will, perceptual behavior control not only affects individual will but also has a direct effect on their behavior (Dakhan et al, 2020;Mirani et al, 2021), which can be confirmed in the empirical results of this research. Furthermore, when the two dimensions jointly affect green purchase intention, the results are similar to the study of Rhodes and Courneya (2003b) that self-efficacy is better at predicting intent than controllability, self-efficacy is the better predictor of intention in this paper which is also endorsed by the studies of (Li, 2020;Elnadi and Gheith, 2021) that the influence of self-efficacy on individual intention cannot be ignored.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Fourth, higher self-efficacy and controllability can bring higher green purchase intention and positive green purchase behavior. As the embodiment of individual will, perceptual behavior control not only affects individual will but also has a direct effect on their behavior (Dakhan et al, 2020;Mirani et al, 2021), which can be confirmed in the empirical results of this research. Furthermore, when the two dimensions jointly affect green purchase intention, the results are similar to the study of Rhodes and Courneya (2003b) that self-efficacy is better at predicting intent than controllability, self-efficacy is the better predictor of intention in this paper which is also endorsed by the studies of (Li, 2020;Elnadi and Gheith, 2021) that the influence of self-efficacy on individual intention cannot be ignored.…”
Section: Discussionsupporting
confidence: 77%
“…Perceived behavioral control is an individual's perception of the degree of difficulty in completing an action, which is affected by self-ability judgment. The stronger perceived behavior control, the stronger belief in the execution of a certain behavior, which can promote the occurrence of behavior (Dakhan et al, 2020;Mirani et al, 2021). When consumers believe that they have enough ability to buy a certain product and have no or less perceived obstacles in the purchase process, their perceived behavioral control will be stronger and they will have more intention to buy green products (Wang et al, 2018).…”
Section: Hypothesis 2b | Injunctive Norm Positively Promotes Green Pu...mentioning
confidence: 99%
“…Simon and Sullivan (1993) view brand equity in two different perspectives; first one is financial perspectives that states and stresses the value of a brand to the firm. The subsequent definition that is from consumer viewpoint emphasizes the value of a brand to the consumers (Rangaswamy et al, 1993;Akhtar et al, 2023;Hongyun et al, 2023;Mirani et al, 2021;. Aaker (1991) and Keller (1993) have discovered brand equity from the consumer perspective based on consumers memory-based brand associations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previously, it has been argued that perceived behavior control is formed by perceived barriers (price, availability) and ability (income or financial resources) that effect green consumption behavior ( Al-Swidi et al, 2014 ; Testa et al, 2019 ). Strong perceived behavioral control leads to a certain behavior that promotes the actual buying behavior ( Mirani et al, 2021 ). When customers trust the sufficiency of their skills to buy a specific product and have fewer hurdles in the buying process, they possess high perceived behavioral control, and their intentions to buy organic products will enhance ( Wang and Li, 2018 ; Sultan et al, 2020 ; Ahmed et al, 2021 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%